Homogeneous BTK Occupancy Assay for Pharmacodynamic Assessment of Tirabrutinib (GS-4059/ONO-4059) Target Engagement. (October 2018) - Yu, Helen; Truong, Hoa; Mitchell, Scott A.; Liclican, Albert; Gosink, John J.; Li, Wanying; Lin, Julie; Feng, Joy Y.; Jürgensmeier, Juliane M.; Billin, Andrew; Xu, Ren; Patterson, Scott; et al.
Bruton's tyrosine kinase (BTK) is a clinically validated target for B-cell leukemias and lymphomas with FDA-approved small-molecule inhibitors ibrutinib and acalabrutinib. Tirabrutinib (GS-4059/ONO-4059, Gilead Sciences, Inc., Foster City, CA) is a second-generation, potent, selective, irreversible BTK inhibitor in clinical development for lymphoid malignancies, including chronic lymphocytic leukemia (CLL) and diffuse large B-cell lymphoma (DLBCL). An accurate pharmacodynamic assay to assess tirabrutinib target coverage in phase 1/2 clinical studies will inform dose and schedule selection for advanced clinical evaluation. We developed a novel duplex homogeneous BTK occupancy assay based on time-resolved fluorescence resonance energy transfer (TR-FRET) to measure free and total BTK levels in a multiplexed format. The dual-wavelength emission property of terbium-conjugated anti-BTK antibody served as the energy donor for two fluorescent energy acceptors with distinct excitation and emission spectra. The assay was characterized and qualified using full-length purified recombinant human BTK protein and peripheral blood mononuclear cells derived from healthy volunteers and patients with CLL. We demonstrated assay utility using cells derived from lymph node and bone marrow samples from patients with CLL and DLBCL. Our TR-FRET-based BTK occupancy assay provides accurate, quantitative assessment of BTK occupancy in the clinical trial program for tirabrutinib and is in use in ongoing clinical studies.